Differential utilization of CARD9 by Dectin-1 in macrophages and dendritic cells2 - Goodridge, Helen S. (2009)
The pattern recognition receptors Toll-like receptor 2 (TLR2) and Dectin-1 play key roles in coordinating the responses of macrophages and dendritic cells (DC) to fungi. Induction of pro-inflammatory cytokines is instructed by signals from both TLR2 and Dectin-1. A recent report identified a role for CARD9 in innate anti-fungal responses, demonstrating CARD9-Bcl10-mediated activation of NF-κB and pro-inflammatory cytokine induction in murine bone marrow-derived DC (bmDC) stimulated via Dectin-1. We now report that Dectin-1-CARD9 signals fail to activate NF-κB and drive TNF-α induction in murine bone marrow-derived macrophages (bmM). However, priming of bmM with GM-CSF or IFN-γ permits Dectin-1-CARD9-mediated TNF-α induction. Analysis of other macrophage/DC populations revealed further variation in the ability of Dectin-1-CARD9 signaling to drive TNF-α production. Resident peritoneal cells and alveolar macrophages produce TNF-α upon Dectin-1 ligation, while thioglycollate-elicited peritoneal macrophages and Flt3L-derived DC do not. We present data demonstrating that CARD9 is recruited to phagosomes via its CARD domain where it enhances TLR-induced cytokine production even in cells in which Dectin-1 is insufficient to drive cytokine production. In such cells, Dectin-1, CARD9 and Bcl10 levels are not limiting, and data indicate that these cells express additional factors that restrict Dectin-1-CARD9 signaling for TNF-α induction.